ASSESSMENT OF WORKING ENVIRONMENT IN READY-MADE GARMENT INDUSTRIES: A CASE STUDY IN GAZIPUR, BANGLADESH - Mahmuda Binte Latif; Shamim Al Mamun; Muliadi Muliadi (Hasanuddin University, 2018)
The study was conducted to assess the ambient environmental condition (temperature, humidity, noise and illumination) in the SIJI Garments Co. Ltd., Ehsan Garments Ltd. and Silver Composite Textile Mills Ltd. in Gazipur District, Bangladesh from September, 2016 to February, 2017 (during winter season) to know the internal working environment of the garment industries. In the SIJI Garments Co. Ltd., the highest temperature was observed in the cutting section (28.7°C), sewing section (28.9°C) and packaging section (29.2°C) which exceeded the guideline values. The highest noise level was observed in packaging section (86.6 dB). The illumination level in the most densely populated sections of workers such as cutting section (450 lux), sewing section (490 lux) and sample section (488 lux) were found unpleasant for the workers. In Ehsan Garments Ltd., the highest temperature was observed in sewing section (26.4°C) which exceeded the ASHRAE (American Society of Heating, Refrigerating and Air Conditioning Engineers)standard and the noise level in sewing section (88.4) which exceeded the ECR guidelines. In Silver Composite Textile Mills Ltd. the illumination level was poor in almost all sections specially cutting (466 lux), sewing (565 lux) and finishing (515 lux) sections where maximum number of workforce was employed. The temperature of all sections of three readymade garment industries were optimum to moderately high, humidity level was around optimum level but the noise levels highly exceeded the ECR, 1997. The illumination level was insufficient especially in the cutting and sewing section.The study revealed that congested work area, improper ventilation, building design, excessive noise, poor illumination, dust and no use of personal protective equipment were the major problem faced by the workers in these industries.